Drawing the lines: the limitations of intercultural ekphrasis - Ramos, M. (Working Images: Visual Research and Representation in Ethnography, 2004)
This paper focuses on the advantages of drawing as a complementary tool both during ethnographic research and in the development of anthropological analysis. It proposes to direct the field of "visual anthropology" in such a way that brings it closer to the valued craft-quality of anthropological discourse, by freeing it from a current technological obsession. Drawing is intimately linked with the act of observing and interpreting human actions. In fact, a trained eye and a skilled hand are basic requirements for proper documentation of both material culture aspects and varied instances of social life, during fieldwork. Also, drawing is an important and creative tool to interact and relate with human beings of different cultures and languages. On the other hand, organizing and integrating information and ideas in graphic terms enables the anthropologist to explore more deeply the complex relational nature of words and images (from opposition tables and kinship schemes to analytical diagrams, drawings and photographs), in order to develop a more encompassing view of the possibilities of anthropological production.